Case Report: Somatic Symptoms Veiling Gender Dysphoria in an Adolescent - Morabito, Giuliana; Cosentini, Dora; Tornese, Gianluca; Gortani, Giulia; Pastore, Serena; Genovese, Maria Rita Lucia; Cozzi, Giorgio (Frontiers in Pediatrics, 2021)
Background: Somatic symptom disorder is common in children and adolescents; usually, it is an expression of a mental health problem or other conditions that lead to psychosocial impairment and suffering. Among these, in pubertal age, gender dysphoria should be considered. Case presentation: We present the case of a 15-year-old girl admitted to the hospital because of a two-month history of scattered arthralgia and myalgia, headache, and fatigue, with repeated visits to the emergency room. The physical exam was unremarkable, except for step walking and pain. Repeated diagnostic tests were normal, and consecutive psychological interviews disclosed intense suffering due to a gender incongruence. Referral to the hospital gender service was offered and refused by the parents. Conclusions: In pubertal age, gender dysphoria may be expressed through somatoform symptoms. Diagnosis is challenging to accept for the parents even in the presence of adequate multi-disciplinary hospital services.